PEMANFAATAN STRATEGI SEGMENTING, TARGETING, DAN POSITIONING PADA LAYANAN JASA CUCI - Pandunegoro, Satria Luhur; Isharina, Ikhtiara Kaideni (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
The objectives of this study are to identify the characteristics of the market segment for Bettercare and to pinpoint the suitable target segments for the wash service business, to which efforts to place the products in the targeted customers’ mind were made. This quantitative descriptive research measures a certain social phenomenon without conducting hypothesis testing. From the population of Bettercare customers in South Tangerang and South Jakarta, using purposive sampling with the criteria of people who have used the company’s helmet washing service at least once, eighty respondents were acquired. The validity and reliability of the research instruments have been assessed. The incorporation of cluster method for the data analysis resulted in that the market segment for Bettercare was service can be classified into two segments: the Confidence Group and the Exclusive Group. Further, the more appropriate segment to be targeted by Bettercare is the Confidence Group.